(3GdGbJUGO GdGSdGej Yde Ge hge? (B/s - (3GHQGgje, ZSGf eMehOs; (3GdbMa, C(B. (3efPQ s ((3HjQhJ(B: s (3OGQ GdacQ GdeYGUQ(B, s, 2000)
(3GdbSe GdChd (B: (3GdGbJUGO GdESdGej Hjf GdTc hGdjbjf (B/ (3ZSGf eMehO EHQGgje (B: (3ebGQfI efgLjI (B: 1. (3GdGbJUGO GdSjGSj ddGbJUGO GdESdGej (B: 2. (3GdUhJ hGdUOi (B: (3JGQjN hCSWhQI (B: 3. (3ajV GdGbJUGO GdESdGej Hjf GdOjf hGdSjGSI (B: (3NGJeI(B-(3GdbSe GdKGfj (B: (3GdGbJUGO GdESdGej YdeG hfXGeG (B/ (3efPQ GdbMa (B: (3ebOeI (B: (3GdaUd GdChd (B: (3GdOjf hGdGbJUGO (B: 1. (3eLGd GdOjf eLGd Yde GdGbJUGO (B: (3GdaUd GdKGfj (B: (3feGPL Yf GdfXQjGJ GdGbJUGOjI GdESdGejI (B: (3GdeHGOF GdESdGejI ddSdhc GdGbJUGOj (B: (3GdaUd GdKGdK (B: (3fXQjI GdJehjd GdESdGej hGdeUQajI GdESdGejI (B: (3ebOeI(B-(3GdbSe GdKGdK (B: (3GdJYbjHGJ (B: (3JYbjH O(B. (3ZSGf EHQGgje Ydi HMK O(B. (3efPQ GdbMa (B: (3JYbjH O(B. (3efPQ GdbMa Ydi HMK O(B. (3ZSGf EHQGgje(B.s
Keywords: (3GbJUGO GSdGejs